NPK macronutrients and microRNA homeostasis - Kulcheski, Franceli R.; Côrrea, Régis; Gomes, Igor A.; de Lima, Júlio C.; Margis, Rogerio (Frontiers in Plant Science, 2015)
Macronutrients are essential elements for plant growth and development. In natural, non-cultivated systems, the availability of macronutrients is not a limiting factor of growth, due to fast recycling mechanisms. However, their availability might be an issue in modern agricultural practices, since soil has been frequently over exploited. From a crop management perspective, the nitrogen (N), phosphorus (P) and potassium (K) are three important limiting factors and therefore frequently added as fertilizers. NPK are among the nutrients that have been reported to alter post-embryonic root developmental processes and consequently, impairs crop yield. To cope with nutrients scarcity, plants have evolved several mechanisms involved in metabolic, physiological and developmental adaptations. In this scenario, microRNAs (miRNAs) have emerged as additional key regulators of nutrients uptake and assimilation. Some studies have demonstrated the intrinsic relation between miRNAs and their targets, and how they can modulate plants to deal with the NPK availability. In this review we focus on miRNAs and their regulation of targets involved in NPK metabolism. In general, NPK starvation is related with miRNAs that are involved in root-architectural changes and uptake activity modulation. We further show that several miRNAs were discovered to be involved in plant–microbe symbiosis during N and P uptake, and in this way we present a global view of some studies that were conducted in the last years. The integration of current knowledge about miRNA-NPK signaling may help future studies to focus in good candidates genes for the development of important tools for plant nutritional breeding.